Sexual Dissatisfaction after Hand Surgery. Issue 10 (24th October 2022) - Rompala, Alexander; Dar, Qurratul-Ain; Avoricani, Alba; Levy, Kenneth H.; Kurtzman, Joey S.; Koehler, Steven M.
Abstract : Background: Using the hand questionnaire (HAND-Q) patient-reported outcome measure, the effects of upper extremity surgery on patients' perception of their sex life were explored. The hand is a uniquely sexual organ, and we hypothesized that self-reported measures of disease severity, quality of life, and emotional impact would correlate with sexual dissatisfaction among patients receiving treatment for hand/upper extremity conditions. Methods: Patients were prospectively enrolled for hand questionnaire participation. Patients with valid responses to the following questions were included: functionality, hand appearance satisfaction, symptom severity, emotional dissatisfaction, sexual dissatisfaction, and treatment satisfaction. Composite scores were created and scored. Sexual dissatisfaction composite scores were compared through Spearman correlation coefficient analysis to quality of life, emotional dissatisfaction, hand appearance, symptom severity, and hand functionality. Results: High levels of diminished quality of life correlated with sexual dissatisfaction (rs = 0.748, P < 0.001). Increased emotional dissatisfaction correlated with sexual dissatisfaction (rs = 0.827, P < 0.001). Increased satisfaction with hand appearance negatively correlated with sexual dissatisfaction (rs = –0.648, P = 0.001). Increased levels of dissatisfaction with hand functionality correlated with sexual dissatisfaction (rs = 0.526, P = 0.005). Conclusions: The correlation between sex life and quality of life may allow surgeons to improve patient satisfaction when treating hand/upper extremity issues. The relationship between sex life and emotional dissatisfaction emphasizes the impact that sexual dissatisfaction has on patients' lives. Evaluating the relationship between hand appearance and sexual dissatisfaction may indicate that patient self-perception of hand attractiveness plays a role in sex life.